'A Little Time Woud Compleat the Cure': Broken Bones and Fracture Experiences of the Working Poor in London's General Hospitals During the Long Eighteenth Century. (30th April 2018) - Mant, Madeleine
Summary: This article draws upon admission and discharge records from four of London's voluntary general hospitals (St Thomas', Guy's, Middlesex and London) to examine the fracture causes and experiences of the working poor. The article reveals that in-patients generally spent sufficient time in the hospital for significant fracture healing to occur. The diagnosis of fracture is considered within the context of Enlightenment medical education, pathological collections and contemporary clinical nosology. Using surgeons' and physicians' clinical notebooks, this article illustrates the fracture treatment received in the voluntary general hospitals and the range of risk factors encountered by the working poor.